Quiconque: vers une moralité anthropologique pour l’individu global: Part 1: "The Human" as the Issue of Anthropology - Rapport, Nigel (Anthropologica, 2022)
"Everyman" was the title of a mediaeval Christian morality play. This article asks how might it be anthropologically possible to inscribe a morality for a universal ego whose capabilities and liabilities were construed not in Christian terms but in existentialist ones. Drawing on notions of the existential that are ethnographic as well as philosophic, the article pursues an answer by developing three arguments, concerning: (1) the capacities of Everyone; (2) an understanding of goodness that relates to space; (3) a mathematics of morality tied to the value of the single human life.